Murine MPDZ‐linked hydrocephalus is caused by hyperpermeability of the choroid plexus - Junning Yang (EMBO Molecular Medicine, 2018)
Abstract Though congenital hydrocephalus is heritable, it has been linked only to eight genes, one of which is MPDZ. Humans and mice that carry a truncated version of MPDZ incur severe hydrocephalus resulting in acute morbidity and lethality. We show by magnetic resonance imaging that contrast medium penetrates into the brain ventricles of mice carrying a Mpdz loss‐of‐function mutation, whereas none is detected in the ventricles of normal mice, implying that the permeability of the choroid plexus epithelial cell monolayer is abnormally high. Comparative proteomic analysis of the cerebrospinal fluid of normal and hydrocephalic mice revealed up to a 53‐fold increase in protein concentration, suggesting that transcytosis through the choroid plexus epithelial cells of Mpdz KO mice is substantially higher than in normal mice. These conclusions are supported by ultrastructural evidence, and by immunohistochemistry and cytology data. Our results provide a straightforward and concise explanation for the pathophysiology of Mpdz‐linked hydrocephalus.